Image-Guided Radiotherapy for Pelvic Cancers: A Review of Current Evidence and Clinical Utilisation. Issue 12 (December 2020) - Webster, A.; Appelt, A.L.; Eminowicz, G.
Abstract: The meticulous selection and utilisation of image-guided radiotherapy (IGRT) are essential for optimal radiotherapy treatment delivery when using highly conformal treatment techniques in pelvic radiotherapy. Pelvic IGRT has several general IGRT issues to consider (such as choice of match strategy, prioritisation between multiple treatment targets and margin estimates) as well as issues specific to pelvic radiotherapy, in particular large inter-fraction organ variation. A range of interventions, including adaptive treatment strategies, have been developed to address these challenges. This review covers general considerations for the clinical implementation of pelvic IGRT in routine practice and provides an overview of current knowledge regarding pelvic inter-fraction organ motion. Published IGRT evidence for each of the major tumour sites (gynaecological, prostate, bladder, rectal and anal cancer) is summarised, as are state-of-the-art adaptive approaches. General recommendations for the implementation of an institutional pelvic IGRT strategy include. Ensuring consistency between treatment intent and the IGRT approach utilised. Ensuring minimum national and international IGRT guidance is followed while considering the benefit of daily volumetric IGRT. Ensuring the appropriate allied health professionals (namely therapy radiographers/radiation therapists) lead on undertaking IGRT. Ensuring the IGRT workflow procedure is clear and includes an escalation process for difficult set-ups. Ensuring a robust IGRT service is in place before implementing advanced adaptive approaches.